Ries impact deposits in the North Alpine Foreland Basin of Germany as a terrestrial analog site for impact-produced seismites and sand spikes on planet Mars - Elmar Buchner; Volker J Sach; Martin Schmieder (AIMS Geosciences)
The North Alpine foreland basin (NAFB) in Germany is characterized by various types of sedimentologic features that make it an excellent terrestrial analog of regions affected by high-energy asteroid impact-quakes on Mars. Impact events have shaped all planetary bodies in the inner Solar System over the past >4 Gyr. The well-preserved Ries impact crater (Baden-Württemberg and Bavaria), formed around 14.8 Ma, has recently been linked to an earthquake-produced seismite horizon in Mid-Miocene NAFB sediments that exhibits typical dewatering structures and is associated with sand spikes, seismically produced pin-shaped pseudo-concretions. In this terrestrial setting, the sand spike tails systematically point away from the Ries crater. On its path across Gale Crater, the Mars rover Curiosity seems to have observed a similar seismite horizon in early Hesperian lacustrine deposits including clastic dikes, convolute bedding, and, likely, sand spikes. Their orientation suggests that the nearby Slagnos impact crater might be the seismic source for the formation of those seismites. The Ries impact–seismite deposits can be traced over a distance of more than 200 km from the source crater (northern Switzerland), which makes the NAFB an excellent terrestrial analog for similar deposits and their sedimentologic inventory within Gale Crater's lake deposits on Mars.